SUPPPORT HEALTH QUALITY THROUGH STUNTING SOCIALIZATION AND PREVENTION IN THE TOURISM VILLAGE, BELITUNG REGENCY: Dukung Kualitas Kesehatan Melalui Sosialisasi dan Pencegahan Stunting Di Desa Wisata Kabupaten Belitung - Azizah, Siti Nur; Yunelsa, Ayesha Azalea; Krisnadi, Zahra; Aziz, Sabilla Rahmaningrum; Wijaya, Dini Hairun Ilmi; Fathaniah, Almas Barizah; Suciati, Iswatun Mei (Universitas Muhamamdiyah Surakarta, 2023)
ABSTRACT Stunting is a failure of growth and development in children under five due to chronic malnutrition. This condition can cause high mortality rates in children under five in Indonesia and Southeast Asia. Keciput Village is a tourism area in Belitung province with abundant natural tourism potential, so this area is very strategic. However, human resources in Keciput has a reasonably high stunting rate compared to other tourism areas. The government has issued various stunting prevention policies through 5 (five) main pillars, namely: Increasing leadership commitment and vision in ministries/agencies, provincial, regional governments, district/city regional governments, and village governments; Improving behavior change communication and community empowerment; Increasing the convergence of specific interventions and sensitive interventions in ministries/agencies, provincial, regional governments, district/city regional governments, and village governments; Improving food and nutrition security at the individual, family, and community levels and Strengthening the development of systems, data, information, research and innovation as well as cross-sectoral policies from the central government to the village level. This community service activity is essential to increase awareness and understanding of stunting and prevention efforts in Keciput Village, Sijuk District, Belitung Regency, Bangka Belitung Islands Province. ABSTRAK Stunting merupakan kegagalan pertumbuhan dan perkembangan pada anak balita akibat kekurangan gizi kronis. Kondisi ini dapat menyebabkan tingginya angka kematian pada anak balita di Indonesia dan Asia Tenggara. Desa Keciput merupakan kawasan wisata di Provinsi Belitung yang memiliki potensi wisata alam yang melimpah, sehingga kawasan ini sangat strategis. Namun, sumber daya manusia di Keciput memiliki angka stunting yang cukup tinggi dibandingkan kawasan wisata lainnya. Pemerintah telah mengeluarkan berbagai kebijakan pencegahan stunting melalui 5 (lima) pilar utama, yaitu Peningkatan komitmen dan visi kepemimpinan di kementerian/lembaga, pemerintah provinsi, pemerintah daerah, pemerintah daerah kabupaten/kota, dan pemerintah desa; Meningkatkan komunikasi perubahan perilaku dan pemberdayaan masyarakat; Meningkatkan konvergensi intervensi spesifik dan intervensi sensitif pada kementerian/lembaga, pemerintah provinsi, daerah, pemerintah daerah kabupaten/kota, dan pemerintah desa; Meningkatkan ketahanan pangan dan gizi pada tingkat individu, keluarga, dan masyarakat dan Memperkuat pengembangan sistem, data, informasi, penelitian dan inovasi serta kebijakan lintas sektor mulai dari pemerintah pusat hingga tingkat desa. Kegiatan pengabdian kepada masyarakat ini penting untuk meningkatkan kesadaran dan pemahaman terhadap stunting dan upaya pencegahannya di Desa Keciput, Kecamatan Sijuk, Kabupaten Belitung, Provinsi Kepulauan Bangka Belitung.